MENINGKATKAN PEMAHAMAN JENIS-JENIS USAHA DALAM MASYARAKAT PADA MATA PELAJARAN IPS MELALUI MODEL INTERAKSI EDUKATIF DI KELAS V SD NEGERI 006 PAGARAN TAPAH DARUSSALAM - Wijiyati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low social studies learning outcomes of fifth-grade students at SD Negeri 006 Pagaran Tapah Darussalam, Rokan Hulu. The study aimed to determine the effectiveness of the Educational Interaction learning model in improving students’ understanding of business activities in society (fishing) in social studies for grade V. The research was conducted for one month. The subjects of this study were all 22 fifth-grade students with heterogeneous academic abilities. The research was a classroom action research (CAR). The instruments used were performance instruments and data collection instruments in the form of teacher and student activity observation sheets. The results of the analysis show that the average initial test score was 59.55. In the first cycle, the score increased to 69.32 and was categorized as medium. In the second cycle, students’ average score increased to 87.05, categorized as very high. This indicates a strong relationship between the increase in teacher and student activities and the improvement of student learning outcomes. These findings show that the Educational Interaction learning model can improve students’ understanding of business activities in the community, particularly in fifth-grade social studies at SD Negeri 006 Pagaran Tapah Darussalam.